Population Structure of Mycosphaerella graminicola and Location of Genes for Resistance to the Pathogen: Recent Advances in Argentina. (16th May 2012) - Simón, María Rosa; Cordo, Cristina A.; Castillo, Nadia S.; Struik, Paul C.; Börner, Andreas
Abstract : Leaf blotch of wheat ( Septoria tritici Rob. ex Desm., teleomorph Mycosphaerella graminicola (Fückel) Schröt. in Cohn) causes significant losses in wheat. During the last decades studies about the genetic variability of the pathogen and location of the resistance have been intensive around the world. The knowledge about the genetic variation of M. graminicola is very important because it could allow us to determine which genotypes predominate within a geographic area. It also can be used to evaluate the germplasm resistance of wheat cultivars with isolates with high genetic differences. In addition, the knowledge of the genes conditioning resistance in different genotypes allows getting precise combination in new germplasm. The incorporation of the known genes in new cultivars could contribute to broadening the resistance to the pathogen. A paper about genetic variability of the pathogen and location of the resistance, with special emphasis in the work carried out in Argentina, is presented.